Gut microbiota profiling reflects the renal dysfunction and psychological distress in patients with diabetic kidney disease - Li, Qi; Xie, Suyi; Liu, Yali; Yue, Wei; Wang, Limin; Liang, Yi; Chen, Yan; Yuan, Huijuan; Yu, Jiawei (Frontiers in Endocrinology, 2024)
Background: The gut microbiota plays a pivotal role in the development of diabetes and kidney disease. However, it is not clear how the intestinal microecological imbalance is involved in the context of diabetic kidney disease (DKD), the leading cause of renal failure. Objectives: To elucidate the gut microbial signatures associated with DKD progression towards endstage renal disease (ESRD) and explore whether they could reflect renal dysfunction and psychological distress. Methods: A cross-sectional study was conducted to explore the gut microbial signatures of 29 DKD non-ESRD patients and 19 DKD ESRD patients compared to 20 healthy controls. Differential analysis was performed to detect distinct gut microbial alterations in diversities and taxon abundance of DKD with and without ESRD. Renal dysfunction was estimated by urea, creatinine, and estimated glomerular filtration rate. Psychological distress was assessed using the Self-Rating Anxiety Scale,